The main activities of curcuminoids: a review (Research, Society and Development, 2022)
Curcumin is a natural ketone widely used in Asia and derived from turmeric (Curcuma longa). Several studies related to the structure and activity of curcumin derivatives have demonstrated molecules with different biological activities, such as antiprotozoal, antifungal, anti-inflammatory, analgesic, anticancer, antioxidant, among others. In this sense, this work sought to carry out a literature review and evaluate the preference of publications of curcumin analogs from the last two decades (2001-2021), with biological activities. The primary research sources adopted were Capes Journal Base, Google Scholar, and ScienceDirect. In the course of the research, dozens of activities were reported by the authors, but, with emphasis on the antioxidant effect, followed by anticancer and anti-inflammatory studies, among articles researched. In this way, this review revealed that much has been focused on the studies of the biological characteristics of curcumins and their derivatives, however, with a preference for activities related to those of great utility for society.